The impact of information systems and technology to the planning function in the Saudi telecoms companies - Elhag, Rahma Elhag Mohamed; Abdelgadir, Mohamednour Eltahir Ahmed; Fait, Adil Mohamed Ahmed; AL-Bashir, Siddiq Mohammed (Edelweiss Applied Science and Technology, 2024)
This study aimed to identify the impact of Information Systems and Technology in the preparation and implementation of plans for telecommunications companies in the Kingdom of Saudi Arabia, through the availability of information in telecoms system, and perceptions of employees of its importance, and determine the relationship between information systems and technology and to identify objectives and develop plans and identify alternatives, implementation and evaluation plans. The study found an effective information necessary elements needed by the physical requirements of humans and technical’s, also showed provide full awareness of the importance of information system among workers in helping to perform the function of planning properly and required a system available. The study also found that there were significant relationship statistically significant differences between the information system and all of the set objectives, develop plans, and identify alternatives to the necessary plans, and implement plans and straightened, according to the Chi-Square Tests, which explained that the value calculated is less than Tabulated value and moral them all level was less than (0.05).